Stay Dead - Henry, April ([Place of publication not identified] : Christy Ottaviano Books-Little Brown and Hachette, 2024)
Entrusted with a key by her dying mother, sixteen-year-old Milan pretends she perished along with her mother as she navigates freezing conditions, outsmarts assassins, and unravels a deadly conspiracy to save herself and others.
New YA book 2024 summer.
Keywords: Mystery and detective stories; Murder; Detective and mystery stories; Conspiracies; Survival